Kesulitan-Kesulitan yang Dihadapi Lansia dalam Mengikuti Program Penyuluhan Kesehatan pada Kelompok Lansia â€œManggisâ€, Padang - Murni, Murni; Ismaniar, Ismaniar (Penerbit Aksara Rentaka Siar (ARS), 2019)
This research is motivated by the phenomenon of the low participation of the elderly in taking part in the health education program for the elderly